2019
DOI: 10.1111/jac.12342
|View full text |Cite
|
Sign up to set email alerts
|

How does the harvest index affect water‐use efficiency and nutrient‐utilization efficiency of sunflowers (Helianthus annuus L.)?

Abstract: Besides oilseed rape and soybean, sunflower is one of the most important annual oilcrops. Apart from seed yield, which is the most important trait in many crops, oil yield is of utmost interest for sunflower breeders and farmers. Compared to the seed yield of sunflowers, their total biomass is often very high, and it is of great agronomic interest to increase the ratio of both parameters, which is defined as harvest index. With an increase in harvest index, improvements of resource‐use efficiencies can be expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The sink size was mainly reduced due to a lower single seed weight under stress (Figure 1c). The higher single seed weight of RGT Llincoln, which was also found by Keipp et al (2019) at maturity, was already observed in the early seed‐filling phase (Figure 1c). These results indicate that RGT Llincoln had a better ability of seed filling than Sy Vivacio already from start of the filling phase.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The sink size was mainly reduced due to a lower single seed weight under stress (Figure 1c). The higher single seed weight of RGT Llincoln, which was also found by Keipp et al (2019) at maturity, was already observed in the early seed‐filling phase (Figure 1c). These results indicate that RGT Llincoln had a better ability of seed filling than Sy Vivacio already from start of the filling phase.…”
Section: Discussionsupporting
confidence: 83%
“…The harvest index is the seed yield relative to the total above‐ground biomass and describes the portion of assimilates that is allocated to the seeds as the harvested product (Hütsch & Schubert, 2017; Wnuk et al, 2014). According to Keipp et al (2019), the harvest index of sunflowers is influenced by both, straw yield and single seed weight. RGT Llincoln had a significantly higher harvest index than Sy Vivacio, caused by a higher total biomass and a lower seed yield of Sy Vivacio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ANR, PE or AE were not identified as priorities for breeding in sunflower. However, Montemurro and De Giorgio (2005) observed differences in NUE for 2 cultivars at field level and recently Keipp et al (2019) in a pot experiment obtained significant differences for the three nutrient-utilization efficiencies (NUE, PUE, and KUE) among 25 sunflower hybrids.…”
Section: Increasing Nutrient Uptake and Use Efficienciesmentioning
confidence: 85%